The The Role of Optimism and Religiosity on Adolescent Happiness - Hamim Rosyidi; Qurrota Ayuni Fitriana (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2023)
Adolescence is a time of transition that is emotionally turbulent. A key component of adolescents' daily lives is happiness. The purpose of this study is to evaluate how optimism and religiosity relate to adolescent happiness. The method used is descriptive quantitative. Research respondents totalled 105 people with an age range of 13 to 18 years at MA PP Darul Hikmah Mojokerto. The optimism scale, religiosity scale and happiness scale were modified and used as the research scales. Multiple regression analysis methods were used to analyze the data. The findings indicated a partially positive relationship between optimism and happiness, with a sig value of 0.000 to 0.05. The relationship between religiosity and happiness is also partially significant, with a sig value of 0.000 to 0.05. While optimism and religiosity have a simultaneous role on happiness with a sig value of 0.000 <0.05, the R square value is 0.421 which means 42.1% there is a role between optimism and religiosity on happiness.